Morphology, anatomy and influence of drying on germination of seeds of Calendula officinalis Morfoanatomía y efecto del secado en la germinación de semillas de caléndula y eneldo - Victoria T. Jorge A.; Sánchez O. Manuel Salvador; Bonilla C Carmen Rosa (Acta Agronómica)
Laboratory tests with seed of Calendula officinalis and Anethum graveolens to describe morphology and anatomy components such as humidity content in balance (CHB) in different atmospheres to get appropriate conservation of the germsplasm to determine physiological behavior in short seed storage to evaluate and to stablish an appropriate methodology for germination, were carried out. The morphological and anatomical description allowed to specify and to illustrate the organs and internal structures of the seed in detail. Also this procedure was important to clarify certain aspects that were managed in wrong way with these species like to confuse the fruit with the seed. It was possible to reach CHB in different atmospheres with artificial drying using the methodology of drying curves with sílica gel in relations of weight-sílica- seed of 10:1, 7:1 and 5:1, besides recommending a method and appropriate relations to conserve the germplasm. The ortodoxal physiological behavior of the seeds of this species was determined.

Germination tests were carried out under different methodologies and materials that statistically didn't show influence on the germination of the seeds. For practical purposes, the sowing methodology in Petri dishes with absorbing paper was recommended. Also this methodology was achieved to identify and to illustrate normal and abnormal plants and seeds of this species that died.

. En semillas de caléndula Calendula officinalis y de eneldo Anethum graveolens, se realizaron la descripción morfológica y anatómica y mediciones del contenido de humedad en equilibrio (CHE). La descripción morfológica y anatómica permitió precisar e ilustrar detalladamente los órganos y tejidos internos de la semilla, además, clarificar aspectos en la definición de semilla pura de caléndula. Se elaboraron curvas de secado y se midió el CHE en diferentes ambientes de secamiento artificial, obtenidos con la metodología de curvas de secado con sílica gel en relaciones de peso sílica-semilla de 10:1, 7:1 y 5:1, además de identificar un método y una relación adecuados para la conservación del germoplasma. Se determinó el comportamiento fisiológico ortodoxo en almacenamiento a corto plazo de las semillas de estas especies. Las diferentes metodologías y sustratos no mostraron diferencia significativa sobre la germinación de las semillas; por facilidad se propone la siembra en cajas Petri con papel absorbente.

Además, se logró tipificar e ilustrar plántulas normales, anormales y semillas muertas.